PEMULIHAN SUHU TUBUH DAN DENYUT JANTUNG DENGAN METODE SPORT MASSAGE DAN STRETCHING STATIS SETELAH BERENANG - Rodhi Rusdianto Hidayat; Ibrahim Ibrahim (SPORT SCIENCE AND EDUCATION JOURNAL, 2021)
The aim of this study was to discover the difference in effectiveness between sports massage, stretching, and conventional recovery in healing body temperature and heart rate after swimming based on the gender of the child. This study used an experimental method with a 2x3 factorial design involving independent variables in the form of the effectiveness of conventional sports massage, stretching, and recovery, and the dependent variables in the form of body temperature and heart rate. We were found that the stretching technique was more effective in restoring body temperature. Meanwhile, conventional massage and recovery techniques are more effective in restoring heart rate. During the Covid-19 pandemic, trainees needed a faster recovery using sports massage and/or conventional recovery methods, to speed up recovery from fatigue and accelerate fitness improvement.